KSU course reader - Malli Raghavan, Karthick Kumar (Kansas State University, 2011)
KSU Course Reader is an android application developed for Kansas State University students to access their course materials, listen to the audio lectures, watch the video lectures and read the lecture slides or other materials from all their enrolled courses with a single application. A student can add RSS xml link associated with the courses enrolled in the current semester in the application and can receive the course materials for each course automatically after every lecture. The aim of this project is to develop a one stop android application for students to access the course materials of all their courses from their android smart phones and tablets. The project also provides a jsp form for course instructors to update the course materials for every lecture which automatically updates the xml file associated with the course. The application also allows students to add other RSS xml like K-State News, K-state Events etc. The same application can be used for adding public rss xml sites and can also be used as a podcast player. It is very essential to provide the course materials readily available to the students all the time wherever they are. Since most students have smart phones or tablets and use them for accessing emails, surf internet etc , it becomes easier for them to use this KSU course reader application to access, read or view all their course materials at one place which is also customized for mobiles and tablets. As android is one of the leading and fastest growing smart phone platforms the project becomes more appropriate to develop in android.
Keywords: Android KSU course reader; Course reader; Computer Science (0984)